St. Vincent and the Grenadines : Report on Observance of Standards and Codes - Basel Core Principles for Effective Banking Supervision-Offshore Banking. (IMF Staff Country Reports; Country Report ;, 2004)
This paper contains a summary assessment of adherence to the Basel Core Principles for Effective Banking Supervision with respect to the offshore sector of St. Vincent and the Grenadines. The St. Vincent and the Grenadines Offshore Finance Authority Act, 1996, and the International Banks Act, 1996, set out the framework for offshore bank supervision in the jurisdiction. The Offshore Finance Authority (OFA) has reportedly enjoyed substantial operational independence. However, it is recommended to enhance OFA's role and legal independence on matters such as the power to set prudential rules administratively.